Analisis English School terhadap Fenomena Terorisme “Islamic State of Iraq and Syria” (ISIS) - Fachrie, Muhammad (Jurnal Ilmu Hubungan Internasional LINO, 2023)
English School argues that the existence of Islamic State of Iraq and Syria (ISIS) phenomena is due to the anarchical Society. This research explains how English School views the main root of security problems is not in perspective of state as focus of inquiry, but it explains how to view the main root of security problems in perspective of Society. It criticizes to the traditional perspectives which only emphasize anarchy as absolute situation or unchangeable thing. This research uses qualitative method which researcher collects data from literatures and analyzes by using theory of English School. In this research, it gives alternative solution to manage international conflict and security caused by the ISIS by building common values, common interests, justices, fairness, communication and dialogue in relations among actors.